2018
DOI: 10.3390/genes9010015
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Analysis of Exonic OCRL Mutations Causing Lowe Syndrome or Dent-2 Disease

Abstract: Mutations in the OCRL gene are associated with both Lowe syndrome and Dent-2 disease. Patients with Lowe syndrome present congenital cataracts, mental disabilities and a renal proximal tubulopathy, whereas patients with Dent-2 disease exhibit similar proximal tubule dysfunction but only mild, or no additional clinical defects. It is not yet understood why some OCRL mutations cause the phenotype of Lowe syndrome, while others develop the milder phenotype of Dent-2 disease. Our goal was to gain new insights into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…The pathogenicity was finally highlighted thanks to mRNA analysis on testis tissue which found aberrant splicing with exon 5 skipping. The exact mechanism of exon skipping remains unknown, even though we suspect modification of Exonic Sequence Enhancer (ESE) which could disturb splicing as it has already been reported for other exonic mutations ( 28 ). This exon skipping should lead to a frameshift and create a premature stop codon downstream (r.830_990del, p.Ala277Aspfs * 11), activating NMD responsible for degrading this allele.…”
Section: Discussionmentioning
confidence: 82%
“…The pathogenicity was finally highlighted thanks to mRNA analysis on testis tissue which found aberrant splicing with exon 5 skipping. The exact mechanism of exon skipping remains unknown, even though we suspect modification of Exonic Sequence Enhancer (ESE) which could disturb splicing as it has already been reported for other exonic mutations ( 28 ). This exon skipping should lead to a frameshift and create a premature stop codon downstream (r.830_990del, p.Ala277Aspfs * 11), activating NMD responsible for degrading this allele.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, it is necessary to study the effects of exonic variants in the SLC12A3 gene of GS on potential splicing, with the discovery of novel variants. In the absence of RNA samples to study alternative splicing, minigene analysis, the effectiveness of which has been confirmed by different studies (Fraile-Bethencourt et al, 2019;Suarez-Artiles, Perdomo-Ramirez, Ramos-Trujillo, & Claverie-Martin, 2018;Takeuchi et al, 2015;Tournier et al, 2008), is still the most direct and credible experimental approach to assess whether a variant influences recognition of an exon and potentially causes phenotypic changes (Bao, Moakley, & Zhang, 2019). In previous studies, we have used this approach to assess the consequences on pre-mRNA splicing of presumed mutations associated with different diseases (Han et al, 2019;Wang et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 84%
“…The literature reveals that the exonic sequences are involved in the regulation of pre-mRNA splicing in addition to their protein-coding potential (53)(54)(55). Because exons contain cis-regulatory elements, such as exonic splicing enhancers (ESEs) and exonic splicing silencers (ESSs) which promote or inhibit the recognition of the neighboring splice sites, respectively (53).…”
Section: Discussionmentioning
confidence: 99%